Pengaruh Kinerja Guru dan Pendayagunaan Sumber Belajar terhadap Prestasi Belajar Siswa - Nurhadi Nurhadi; Abdul Azis (PALAPA, 2020)
This study aims to see whether there is an influence on teacher performance and the utilization of learning resources on student achievement in the field of Islamic Education in Private Junior High Schools in the Bukit Raya District of Pekanbaru City. The population in this study were all VII grade students of Private Junior High Schools in the Bukit Raya District of Pekanbaru, which amounted to 323 people. The sample in this study was taken by proportionate random sampling technique with Slovin formula that is 173 people. Data collection was carried out using a questionnaire technique, the data collected was analyzed using multiple regression analysis namely Y = a + b1X1 + b2X2. The results of this study indicate the value of R2 (coefficient of determination) or R Square of 0.284 or 28.4%. This value can be interpreted that changes in student achievement by changes in the value of the independent variable teacher performance and the utilization of learning resources by 28.4% while 71.6% is determined by changes in other factors. Tcount value for learning motivation variable is 3.529 with sig. 0.001 smaller than 0.05 this means that there is an influence of teacher performance on student achievement and tcount for the utilization of learning resources variable is 3,659 with sig. 0,000 is less than 0.05, this means that there is an influence of the use of learning resources on student achievement. It can be concluded that there is an influence between teacher performance and the utilization of learning resources on student achievement in the field of Islamic Education in Private Junior High Schools in the Bukit Raya District of Pekanbaru City.